2009
DOI: 10.1021/es802910z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Sequestration in Cement Kiln Dust through Mineral Carbonation

Abstract: Carbon sequestration through the formation of carbonates is a potential means to reduce CO2 emissions. Alkaline industrial solid wastes typically have high mass fractions of reactive oxides that may not require preprocessing, making them an attractive source material for mineral carbonation The degree of mineral carbonation achievable in cement kiln dust (CKD) underambienttemperatures and pressures was examined through a series of batch and column experiments. The overall extent and potential mechanisms and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(193 citation statements)
references
References 22 publications
5
178
0
Order By: Relevance
“…Prior studies show only minor variation in this utilization fraction across regions (<4.5%; Supplementary Data3). Cement kiln dust (CKD) related to clinker production 14,15 (Supplementary Table 4) will absorb carbon dioxide during landfill/waste treatment 16,17 , as will cement waste generated in construction.…”
Section: Cement Constituents and Hydration Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies show only minor variation in this utilization fraction across regions (<4.5%; Supplementary Data3). Cement kiln dust (CKD) related to clinker production 14,15 (Supplementary Table 4) will absorb carbon dioxide during landfill/waste treatment 16,17 , as will cement waste generated in construction.…”
Section: Cement Constituents and Hydration Reactionsmentioning
confidence: 99%
“…Given the very small particle size, substantial carbonation occurs within the first 2 days of reaction in a landfill and complete carbonation is achieved within one year 16,17 . We estimate carbon uptake by CKD in different regions of the world based on the cement production, CKD generation rate, proportion of CKD treatment in landfill (Supplementary Data4), CaO proportion in CKD 14 , and the fraction of CaO within fully carbonated CKD that has been converted to CaCO 3 (see method).…”
Section: Carbon Uptake By Cement Kiln Dustmentioning
confidence: 99%
“…The common mineralogy of BOF slag includes olivine, merwinite, C 3 S (tricalcium silicates), larnite (C 2 S, dicalcium silicates), C 4 AF, C 2 F, RO phase (CaOFeO -MgO solid solution), free lime (CaO), and periclase (MgO) (Shi and Qian, 2000;Costa, 2009;Birat, 2009). Free lime (as much as 6% in total) in steelmaking slag comes from two sources: residual free lime from the raw material Rendek et al, 2006;Li et al, 2007;Huntzinger et al, 2009a;Chang et al, 2011a, b …”
Section: Alkaline Wastes As Adsorbentsmentioning
confidence: 99%
“…The potential advantages of accelerated carbonation of applied industrial alkaline solid wastes include: (a) carbonation is an exothermal reaction and hence energy consumption and costs may be reduced by its inherent properties; (b) carbonation products such as calcium or magnesium carbonates are thermodynamically stable under ambient conditions, that is, in the absence of acidification. ; (c) it offers great sequestration capacity due to the high availability of deposits; (d) it does not require transport at sites within steel-works and is therefore cost-effective; (e) products may be beneficially reused in a variety of application, such as construction materials; (f) carbonation eliminates environmental impacts due to decreased leaching of heavy metal trace elements such as Pb, Ni, and Cd from residues and stabilizing of the waste leading to an improvement of environmental quality; and (g) it could neutralise the pH of the solution as carbonate precipitations are formed if alkaline wastewater is used as the liquid agents (Lackner, 2003;Fernandez-Bertos et al, 2004a;Huijgen et al, 2005b, c;Costa et al, 2007;Eloneva et al, 2008a;Bonenfant et al, 2009;Huntzinger et al, 2009a;Gunning et al, 2010;Lim et al, 2010). This paper focuses on accelerated carbonation of industrial alkaline wastes, e.g., steelmaking slags and metalworking wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Various sources of alkalinity have been suggested for CO 2 sequestration purposes. For example, alkaline solid residues from different industries such as steel slag (Huijgen & Comans, 2005;Kelly et al, 2011), cement kiln dust (Huntzinger et al, 2009), and fly ashes (Back et al, 2008;Costa et al, 2007), have been identified as alkalinity sources. The quantity and distribution of these alkaline solid wastes is however limited on a global scale (Huijgen & Comans, 2005).…”
Section: Alkalinity Source For Conversion Of Co 2 To Carbonate Ionsmentioning
confidence: 99%